THE THE EFFECT OF ETHREL SOLUTION IN RIPENING PROCESS ON THE QUALITY OF PAPAYA FRUIT (Carica papaya L) - Almira Ulimaz (Nusantara Hasana Journal, 2021)
Papaya fruit is one source of vegetable protein. This fruit is often cultivated because of its considerable benefits for health. In addition to cultivating papaya plants, farmers also often ripening papaya fruit that has been harvested using ethrel solution. This study aims to describe the effect of The Addition of ethrel solution on the quality of papaya fruit. This research is an experimental study consisting of 5 treatments and 3 replications with a test model that is an organoleptic test to measure the quality of papaya fruit. Research data presented descriptively. The results showed that administration of Ethrel solution affected the quality of papaya fruit with optimal concentration in the treatment of P3 or 0.6% Ethrel per liter of water. Papaya fruit has the best color, texture, and taste in the P3 treatment when compared with the P0, P1, P2, P4, and P5 treatments. The best length of days in the ripening process is five days.